Absorption Resonance Energy Transfer Between Organic Dyes (Cumarin And Rohdamain ) - Abdle Diam, Wajeha; ., . (International Journal of Engineering and Technology, 2018)
The spectral properties absorption of laser dyes (C480 & R610) mixture have been studied; this type of laser dye belongs to the coumarinoids and Xanthenes family, and has been dissolved in ethanol to prepare (1:1, 1:2, 1:3, 1;4, ratio) from Cumarin 480(C48): Rohdamin610 (R610) in (10-4 10-5 ,10-6 ) M/L concentration at room temperature. The achieved results pointed out to an increase in the absorption intensities with the increased concentration of R610 from(10-6,10-5 to 10-4 M/L the same thing for C480 which are found in agreement with Beer – Lambert law and theachieved Results pointed that the absorption peak are moving toward short wavelengths(BLUE SHIFT) when increasing the ratio of concentration.